Culture shapes eye movements for visually homogeneous objects - Kelly, David J.; Miellet, Sebastien; Caldara, Roberto (Frontiers in Psychology, 2010)
Culture affects the way people move their eyes to extract information in their visual world. Adults from Eastern societies (e.g., China) display a disposition to process information holistically, whereas individuals from Western societies (e.g., Britain) process information analytically. In terms of face processing, adults from Western cultures typically fixate the eyes and mouth, while adults from Eastern cultures fixate centrally on the nose region, yet face recognition accuracy is comparable across populations. A potential explanation for the observed differences relates to social norms concerning eye gaze avoidance/engagement when interacting with conspecifics. Furthermore, it has been argued that faces represent a ‘special’ stimulus category and are processed holistically, with the whole face processed as a single unit. The extent to which the holistic eye movement strategy deployed by East Asian observers is related to holistic processing for faces is undetermined. To investigate these hypotheses, we recorded eye movements of adults from Western and Eastern cultural backgrounds while learning and recognizing visually homogeneous objects: human faces, sheep faces and greebles. Both group of observers recognized faces better than any other visual category, as predicted by the specificity of faces. However, East Asian participants deployed central fixations across all the visual categories. This cultural perceptual strategy was not specific to faces, discarding any parallel between the eye movements of Easterners with the holistic processing specific to faces. Cultural diversity in the eye movements used to extract information from visual homogenous objects is rooted in more general and fundamental mechanisms.